Compiling ship and airborne measurements for the Antarctic's second-generation magnetic anomaly map - Golynsky Alexander; Golynsky Dmitry; von Frese Ralph (Russian Journal of Earth Sciences, 2022)
In 2001, the Antarctic Digital Magnetic Anomaly Project produced the ADMAP-1 compilation that included the first magnetic anomaly map of the region south of 60◦S. To help fill ADMAP-1’s regional coverage gaps, the international geomagnetic community from 2001 through 2014 acquired an additional 2.0+ million line-km of airborne and marine magnetic anomaly data. These new data together with surveys that were not previously in the public domain significantly upgraded the ADMAP compilation for Antarctic crustal studies. The merger of the additional data with ADMAP-1’s roughly 1.5 million line-km of survey data produced the second-generation ADMAP-2 compilation. The present study comprehensively reviews the problems and progress in merging the airborne and ship magnetic measurements obtained in the harsh Antarctic environment since the first International Geophysical Year (IGY 1957–58) by international campaigns with disparate survey parameters. For ADMAP-2, the newly acquired data were corrected for the diurnal and International Geomagnetic Reference Field effects, edited for high-frequency errors, and levelled to minimize line-correlated noise. ADMAP-2 provides important new constraints on the enigmatic geology of the Gamburtsev Subglacial Mountains, Prince Charles Mountains, Dronning Maud Land, and other poorly explored Antarctic areas. It links widely separated outcrops to help unify disparate geologic and geophysical studies for new insights on the global tectonic processes and crustal properties of the Antarctic. It also supports studies of the Antarctic ice sheet’s geological controls, the crustal transitions between Antarctica and adjacent oceans, and the geodynamic evolution of the Antarctic crust in the assembly and break-up of the Gondwana and Rodinia supercontinents.